Desacetyl-α-melanocyte stimulating hormone and α-melanocyte stimulating hormone are required to regulate energy balance - Kathleen G. Mountjoy; Alexandre Caron; Kristina Hubbard; Avik Shome; Angus C. Grey; Bo Sun; Sarah Bould; Martin Middleditch; Beau Pontré; Ailsa McGregor; Paul W.R. Harris; Renata Kowalczyk; et al. (Elsevier, 2018)
Objective: Regulation of energy balance depends on pro-opiomelanocortin (POMC)-derived peptides and melanocortin-4 receptor (MC4R). Alpha-melanocyte stimulating hormone (α-MSH) is the predicted natural POMC-derived peptide that regulates energy balance. Desacetyl-α-MSH, the precursor for α-MSH, is present in brain and blood. Desacetyl-α-MSH is considered to be unimportant for regulating energy balance despite being more potent (compared with α-MSH) at activating the appetite-regulating MC4R in vitro. Thus, the physiological role for desacetyl-α-MSH is still unclear. Methods: We created a novel mouse model to determine whether desacetyl-α-MSH plays a role in regulating energy balance. We engineered a knock in targeted QKQR mutation in the POMC protein cleavage site that blocks the production of both desacetyl-α-MSH and α-MSH from adrenocorticotropin (ACTH1-39). Results: The mutant ACTH1-39 (ACTHQKQR) functions similar to native ACTH1-39 (ACTHKKRR) at the melanocortin 2 receptor (MC2R) in vivo and MC4R in vitro. Male and female homozygous mutant ACTH1-39 (Pomctm1/tm1) mice develop the characteristic melanocortin obesity phenotype. Replacement of either desacetyl-α-MSH or α-MSH over 14 days into Pomctm1/tm1 mouse brain significantly reverses excess body weight and fat mass gained compared to wild type (WT) (Pomcwt/wt) mice. Here, we identify both desacetyl-α-MSH and α-MSH peptides as regulators of energy balance and highlight a previously unappreciated physiological role for desacetyl-α-MSH. Conclusions: Based on these data we propose that there is potential to exploit the naturally occurring POMC-derived peptides to treat obesity but this relies on first understanding the specific function(s) for desacetyl-α-MSH and α-MSH. Keywords: POMC, Obesity, Desacetyl-α-MSH, α-MSH, Obese mouse model